THE IMAGE OF THE CHILD IN THE OPENING OF THE SPIRITUAL AND MORAL WORLD OF ADULTS: INTERPRETATION AND IMAGE (Journal of Science-Innovative Research in Uzbekistan, 2024)
Uzbek literature has always reflected the life of society throughout its rich and colorful history. The image of the child's image occupies a special place in this process. Through the image of a child, ADIBS show the complexity of the adult world, the influence of the social environment and the essence of personal relationships. The image of a child is important in opening the spiritual and moral world of adults. The child often appears as a symbol of innocence, sincerity and life values. Through the image of a child, the writer shows the spiritual and moral aspects of the adult world, their internal contradictions. Through the relationship of adults with the child, their moral values, worldview and mental state are analyzed